After-education : Anna Freud, Melanie Klein, and psychoanalytic histories of learning - Britzman, Deborah P., 1952- (State University of New York Press, 2003)
"In After-Education Deborah P. Britzman raises the startling question, What is education that it should give us such trouble? She explores a series of historic and contemporary psychoanalytic arguments over the nature of reality and fantasy for thinking through the force and history of education. Drawing from the theories of Anna Freud and Melanie Klein, she analyzes experiences of difficult knowledge, pedagogy, group psychology, theory, and questions of loneliness in learning education. Throughout the book, education appears and is transformed in its various guises as a nervous condition, as social relation, as authority, as psychological knowledge, as quality of physical reality, as fact of natality, as the thing between teachers and students, as an institution, and as a play between reality and fantasy."--Jacket
Keywords: Freud, Anna, -- 1895-1982.; Klein, Melanie.; Freud, Anna, -- 1895-; Freud, Anna, -- 1895-1982; Klein, Melanie; Klein, Melanie, -- 1882-1960.; Psychoanalysis and education.; Learning, Psychology of.; Psychanalyse et éducation.; Psychologie de l'apprentissage.; EDUCATION -- Educational Psychology.; Learning, Psychology of; Psychoanalysis and education; Psychoanalyse.; Leren.; Éducation.; Psychanalyse.